Cellular therapy for the peripheral arterial disease treatment: Protocol for a systematic review and meta-analysis - Mónica Rodríguez-Valiente; Cristina Fuente-Mora; Javier Sánchez-Gálvez; Micaela Ortín-Pérez; Manuel Pardo-Ríos; José Manuel Sánchez-Sáez; Isac Davidson Santiago Fernandes Pimenta; Grasiela Piuvezam; Laura Ramos-Petersen (PLoS ONE, 2025)
Cellular therapy is a promising treatment option for Peripheral Arterial Disease (PAD). Different cell types can be used to regenerate and repair tissues affected by PAD. Many studies have proposed the use of stem cells, such as mesenchymal stem cells, or even mononuclear cells isolated from peripheral blood or bone marrow, to treat PAD. This paper reports a protocol of systematic review and meta-analysis that aims to identify the effects of stem cell treatment in patients with peripheral arterial disease. The search will be conducted in the following database: PubMed/MEDLINE, Clinicaltrial.gov, Scopus, Embase, Epistemonikos, Web of Science and Cochrane Library. Studies will be selected independently by two reviewers and will include all published randomized and non-randomized clinical trials. The data extraction will include studies population characteristics, type of treatment and main outcomes. We will assess the methodological quality of the studies using the Cochrane Risk of Bias 2.0 and Risk of Bias in Non-randomized Studies of Interventions. The certainty of the evidence will be rate using the Grading of Recommendations, Assessment, Development, and Evaluations. The findings will be presented in narrative summary tables and in a meta-analysis.